“THE CARPATHIAN MOUNTAINS”: LOVE, FATE, AND EXISTENTIAL TENTIONS IN ALEKSANDR FAYNBERG’S POETIC UNIVERSE - ODILOVA CHAROSXON SHAVKATJON KIZI, (TADQIQOTLAR, 2026)
ANNOTATION: This article provides a comprehensive, systematic, and multi-method  scholarly  analysis  of  Aleksandr  Faynberg’s  poem  “The  Carpathian Mountains.” The study examines the poem’s poetic structure, compositional dynamics, symbolic-semiotic  system,  ontological  and  axiological  layers,  existential  tensions, poetics of love and fate, psychological mechanisms of the inner monologue, and socio-philosophical implications. Through images such as the Carpathian mountains, lovers, stars,  the  Jewish  young  man,  and  local  Gutsul  customs,  the  poem  explores  love, destiny, moral responsibility, and the human confrontation with tragic fate. Methodologically, the research relies on structuralism, hermeneutics, semiotics, phenomenology, and existential analysis. The poem is interpreted as a multilayered poetic model articulating the tension between individual desire, social context, and universal fate.